Utilization Of Livestock Waste As A Realization Of Green Economy Of The Village Community Of Kesik, Masbagik District, East Lombok (Jurnal Wicara, 2025)
The 2024/2025 Community Service Program (KKN) of the University of Mataram was implemented in Kesik Village, Masbagik District, West Nusa Tenggara (NTB), with a focus on the utilization of livestock waste as a manifestation of the local community's green economy. The majority of the people of Kesik Village work as farmers and ranchers, but this village faces problems related to the processing of livestock waste which has a negative impact on the environment and public health. This program aims to provide education and training to the community to process livestock waste, especially cow waste, into organic solid fertilizer. Activities include socialization, practical training, and ongoing monitoring and evaluation. The results of this activity show success in teaching the community how to process livestock waste into organic manure. Routine monitoring is carried out to ensure that the fermentation process and production of organic manure run according to established procedures. With this program, it is hoped that it can empower the people of Kesik Village to process livestock waste into fertilizer that is beneficial for the agricultural sector and reduce the negative impact of waste on the environment.
Keywords: Animal Waste; Organic Fertilizer; Kesik Village